2013
DOI: 10.3324/haematol.2012.079707
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for children with high-risk acute lymphoblastic leukemia in first complete remission: a report from the AIEOP registry

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n N o c o m m e r c i a l u s eThe dynamic evolution of the results obtained with chemotherapy protocols has led to relevant modifications of the eligibility criteria for allogeneic hematopoietic stem cell transplantation (HSCT), so that, for instance, patients with B-cell precursor ALL and more than 100x10 9 /L white blood cells at diagnosis not responding to the steroid prephase should not be offered transplantation.Several retrospective studies suggested that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
5
27
0
Order By: Relevance
“…Second, as this study is monocentric, patients in this study did not receive various combinations of immunosuppressive agents as usually reported. 25,28,30,35,54 MRD before HSCT had no prognostic value in our cohort. The DFS of patients with negative or positive MRD before HSCT was similar.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Second, as this study is monocentric, patients in this study did not receive various combinations of immunosuppressive agents as usually reported. 25,28,30,35,54 MRD before HSCT had no prognostic value in our cohort. The DFS of patients with negative or positive MRD before HSCT was similar.…”
Section: Discussionmentioning
confidence: 71%
“…DFS usually reported in children transplanted for high-risk leukemia from sibling or unrelated donors vary between 50 and 70%. 25,[27][28][29][30][31][32][33]40 Weiss et al 37 report a similar DFS (84%) using CsA alone as GVHD prophylaxis but in patients transplanted only from MSDs. 37 They also used CsA while targeting a lower and narrower TBC range (80-130 ng/mL) compared with those usually recommended (100-200 ng/mL).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations